IMPLEMENTASI METODE RELIABILITY CENTERED MAINTENANCE PADA KOMPONEN KRITIS TURBIN UAP DI PT MADUBARU - Maria Eva Susanti Lelu; Widya Setiafindari (Universitas Islam Nahdlatul Ulama Jepara, 2023)
IMPLEMENTATION OF RELIABILITY CENTERED MAINTENANCE METHOD ON CRITICAL COMPONENTS OF STEAM TURBINE AT PT MADUBARUSteam turbine is a machine that can be used to convert heat energy from steam into mechanical energy so that it can produce electrical energy. As a source of electrical energy, PT Madubaru utilizes this steam turbine. The purpose of this research is to determine the Mean Time To Failure or MTTF and Mean Time To Repair or MTTR values and which components of this steam turbine have the highest Risk Priority Number (RPN) based on FMEA analysis. This study uses FMEA analysis and the Reliability Centered Maintenance (RCM) method. From the results of data processing that has been done it is known that the most critical component is the coupling component with a damage percentage level of 21.62% of the other components. Based on the calculation of the MTTF value, the result is 1863.74, this means that the coupling component needs to be maintained or checked after operating for 1863.74 hours or around 77,656 days. In addition, for the calculation of the MTTR value, the result is 0.7941 hours, which means that the coupling component takes 0.7941 hours to repair. While the FMEA analysis showed that the coupling component received the highest RPN value of 24 out of the other components. The cause that occurred was due to a broken coupling membrane which hampered the production process because it was necessary to repair the component.